2019
DOI: 10.3390/nu11122849
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions with a Focus on Nutritional Strategies to Increase Cardiorespiratory Fitness in Chronic Obstructive Pulmonary Disease, Heart Failure, Obesity, Sarcopenia, and Frailty

Abstract: Cardiorespiratory fitness (CRF) is an independent predictor for all-cause and disease-specific morbidity and mortality. CRF is a modifiable risk factor, and exercise training and increased physical activity, as well as targeted medical therapies, can improve CRF. Although nutrition is a modifiable risk factor for chronic noncommunicable diseases, little is known about the effect of dietary patterns and specific nutrients on modifying CRF. This review focuses specifically on trials that implemented dietary supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 154 publications
(290 reference statements)
2
30
0
1
Order By: Relevance
“…The prevalence of SO has been reported to be higher in patients with chronic diseases such as hypertension, diabetes, abnormal lipid metabolism. [18][19][20][21] The results of this study also indicate that the participants in the SO group were older than the those in the non-SO group, suggesting that increasing age may be a risk factor for the occurrence of SO. 22,23 The participants in the SO group were shorter; had faster heart rate; heavier weight; lower WC, BMI, TG, TC, LDL-C, and higher HDL-C; and lower education level than those in the non-SO group.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The prevalence of SO has been reported to be higher in patients with chronic diseases such as hypertension, diabetes, abnormal lipid metabolism. [18][19][20][21] The results of this study also indicate that the participants in the SO group were older than the those in the non-SO group, suggesting that increasing age may be a risk factor for the occurrence of SO. 22,23 The participants in the SO group were shorter; had faster heart rate; heavier weight; lower WC, BMI, TG, TC, LDL-C, and higher HDL-C; and lower education level than those in the non-SO group.…”
Section: Discussionsupporting
confidence: 55%
“…The prevalence of SO has been reported to be higher in patients with chronic diseases such as hypertension, diabetes, abnormal lipid metabolism. 18–21 …”
Section: Discussionmentioning
confidence: 99%
“…The 6-minute-walking-test (6MWT) is one of the recommended tools for assessment of muscular strength in the European consensus statement on definition and diagnosis of sarcopenia [41]. In HF patients, sarcopenia may have a greater negative impact on tolerance of exertion and quality of life than cachexia [42]. Some authors state that HF patients tend to lose muscular tissue prior to fatty tissue, and that sarcopenia may contribute to development of or precede cachexia, which in turn is related to loss of muscular, fatty, and bone tissues [43].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it can be stated that diet consideration and monitoring the obesity rate should be an important part of the health campaigns that are promoted to disrupt the triggering of developing COPD [28]. Compelling evidence supports that the fundamental problem beyond obesity: diet, and its influence has been provided in the research, followed by a comprehensive understanding of diet and obesity and their influence on COPD [4,8,24]. Research driven nutrient reports about the pathogenesis of COPD demonstrated that incorrect diet and obesity along with a viable intervention has also been provided in the research [28].…”
Section: Introductionmentioning
confidence: 99%